Development of Integrated Thematic Teaching Materials with the Discovery Learning Model Using Adobe Flash CS6 Interactive Multimedia - Hanafi Hanafi; Andre Satrio; Desyandri Desyandri; Risda Amini; Daharnis Daharnis (Jurnal Penelitian Pendidikan IPA, 2024)
The use of teaching materials in elementary schools is not optimal, teachers tend to only use students' books as teaching materials. To overcome this problem, integrated thematic teaching materials were developed with the Discovery Learning model using interactive multimedia Adobe Flash CS6 in class V of elementary schools. This research aims to develop integrated thematic teaching material products with the Discovery Learning model using interactive multimedia Adobe Flash CS6. This research uses research and development (R&D) methods with the ADDIE development model. In the ADDIE development model there are five main stages, namely Analysis, Design, Development, Implementation, and Evaluation. Validation is carried out to determine the suitability of the teaching materials developed. The material aspect obtained 91.81% in the very valid category, the media aspect obtained 90.83% in the very valid category, and the language aspect obtained 96% in the very valid category. At the Implementation stage, practicality tests and effectiveness tests are carried out. The results of the practicality test with teachers obtained an average of 95%, by teachers and 86% by students in the very practical category. Effectiveness testing was carried out on aspects of student motivation and learning outcomes. The motivation aspect obtained an average of 83% in the very high category. Learning outcomes in the knowledge aspect, posttest scores at SDN 09 Selayo were 82.66 with a Good predicate, and at SDN 24 Selayo 85.33 with a Good predicate. From the research conducted, it can be stated that integrated thematic teaching materials with a discovery learning model using Adobe Flash CS6 interactive multimedia are valid, practical and effective for use in class V elementary schools